Technology and Livelihood Education (TLE) During In-Person Classes: Experiences of Secondary School Teachers - Taripe, April Lloyd C. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological inquiry explored the experiences of secondary school teachers teaching TLE subject during the in-person classes in public secondary schools, Division of Tagum City. I employed qualitative – phenomenological study in exploring the experiences of the ten (10) participants of which primary instrument of data gathering was through in- depth interview. Major findings revealed on their experiences in teaching TLE subject during the in-person classes, after analyzing their responses, the following were the emergent themes namely effective teacher-student relationships, acquisition of necessary skills, and teachers’ competence on the subject. Furthermore, the challenges of the participants were learning loss and job mismatch. It can be noted that these challenges were critical for the secondary teachers in teaching the TLE subject. Finally, in terms of their insights in teaching TLE subject during the in-person classes drawn from the findings of the study, the emergent themes were holistic curriculum, enhancement of 21st century skills, and provision of high-quality instruction. Results imply that by helping students become more proficient in a variety of life skills and applications of technology, the TLE Department strives, in accordance with the vision and objective of the school, to foster entrepreneurial spirit, critical thinking, self-reliance, independence, cultural sensitivity, and self-sufficiency in its student body. However, a mismatch between skills and responsibilities on the job has a detrimental impact on both the macroeconomic and the microeconomic levels of work productivity. It should come as no surprise that human resources that have a high level of education, qualification, and skills but do not make use of them constitute a waste of resources and a possible missed opportunity for employment.